2018
DOI: 10.1103/physrevb.97.241413
|View full text |Cite
|
Sign up to set email alerts
|

Coherence of a dynamically decoupled quantum-dot hole spin

Abstract: A heavy hole confined to an InGaAs quantum dot promises the union of a stable spin and optical coherence to form a near perfect, high-bandwidth spin-photon interface. Despite theoretical predictions and encouraging preliminary measurements, the dynamic processes determining the coherence of the hole spin are yet to be understood. Here, we establish the regimes that allow for a highly coherent hole spin in these systems, recovering a crossover from hyperfine to electrical-noise dominated decoherence with a few-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 34 publications
1
39
0
Order By: Relevance
“…The grey solid lines show the results obtained from Eq. (14). In order to relate our multi-band numerical wave functions to the simple theory we define here the wave function participation number as…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The grey solid lines show the results obtained from Eq. (14). In order to relate our multi-band numerical wave functions to the simple theory we define here the wave function participation number as…”
Section: Resultsmentioning
confidence: 99%
“…assuming the same envelope shapes for holes and electrons) and all the multi-band effects (including the degree of heavy-light hole mixing), and their relation to QD shape. This includes works on carrier spin coherence (which apart from nuclear effects show influence of charge noise coupling to spin via electric-field dependent g-factors [11,14]), creation of dynamic nuclear polarization [4,5], and optical detection (through changes in Overhauser field-induced spin splitting of electron and holes) of nuclear magnetic resonance of different species of nuclei present in the dot [31]. While such experiments were used to obtain new information on structural properties and strain distribu-tion in QDs [31], the simplicity of some of the abovementioned assumptions casts a certain degree of doubt on the interpretation of measurement results.…”
Section: Introductionmentioning
confidence: 99%
“…In spin echo measurements, coherence times of T2SE13μs have been observed for electrons and holes, indicating the presence of charge noise limiting the observed coherence times. To these ends, dynamical decoupling has recently been demonstrated to enhance achievable T 2 times . In addition, it was recently shown that preparing the nuclear spin bath in a subthermal state using optical techniques allows to increase T2 by more than one order of magnitude .…”
Section: Single Photons Entangled With Spinsmentioning
confidence: 99%
“…However, in a temporal or spatial ensemble, the Overhauser field is randomly distributed leading to fast dephasing of electron spins with T22ns . Due to their p‐like central cell wavefunction holes have a weaker hyperfine contact interaction and consequently more than one order of magnitude longer T2 have been reported in time domain experiments and in frequency domain measurements (coherent population trapping) for holes T2 times approaching one microsecond were reported . On intermediate timescales of hundreds of ns, the Overhauser field coherently evolves in time due to the quadrupolar moments resulting from the strained nuclei .…”
Section: Single Photons Entangled With Spinsmentioning
confidence: 99%
See 1 more Smart Citation